Filmes finos de titanato de bário estrôncio para a produção de dispositivos eletrônicos - Ávila, Ana Paula Araújo Albuquerque (2023)
The use of Barium Strontium Titanate (BST) thin films has gained increasing importance due to it’s optical and ferroelectric properties, as well as high dielectric constant and low dielectric loss, good electrical conductivity and thermal stability, which make them ideal for application in electronic devices such as dynamic memories (DRAMs and FRAMs), integrated circuits, actuators, solar cells, infrared sensors, waveguides, among others. The study of BST thin films has been mainly focused on optimizing their properties. The objective of this work is the deposition of amorphous BST thin films at room temperature using the RF Magnetron Sputtering technique and thermally treat them for subsequent crystallization. The thickness of the films and their respective deposition rates were determined by Profilometry, their surface morphology was characterized by Scanning Electron Microscopy (SEM) and their optical properties determined by Ultraviolet and Visible Spectrophotometry (UV-Vis), using the Swanepoel and Tauc methods. XRD analysis allowed the identification and characterization of the crystalline phases present in the films by refining the diffractograms by the Rietveld method, as well as estimating the average crystallite size and the lattice microstrain by the WiliamsonHall method. From the analysis of data obtained in the characterization of BST thin films heattreated at 700°C for 1 hour, it was observed that the peaks of higher intensity in the 110 and 200 directions indicate the preferential orientation in the BST thin films. Furthermore, through Rietveld refinement, it was observed that the films, after heat treatment, presented a cubic Pm3̅m or tetragonal P4mm crystalline phase (with in-plane distortion, i.e., c<a). The tetragonal (or pseudocubic with in-plane distortion) phase is probably caused by defects in the crystal structure. The lattice parameters for all films after heat treatment were higher than that obtained for bulk BST, which is consistent with the presence of oxygen vacancies. The tetragonal distortion observed in the BST thin films deposited in this work is capable of altering the properties of the material, making it a possible candidate for application in electronic devices.